Comparative study: normotensive and preeclampsia mother presenting with imminent symptoms of eclampsia in third trimester of pregnancy - C., Raji; S., Suba (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: This prospective study compares the maternal and fetal outcome in normotensive and preeclampsia mother presenting with imminent symptoms of eclampsia in third trimester. This prospective study was conducted in the department of obstetrics and gynaecology, Government Theni Medical College, Tamil Nadu, India in 2019. Methods: A total 100 antenatal mothers were selected for the study. Group A - 50 known case of preeclampsia presented with imminent symptoms. Group B-50 previously normotensive patients present with imminent symptoms of eclampsia. Maternal and fetal outcome were analysed. Results: Incidence of eclampsia - 0.1%, HELLP syndrome - 0.04%, pulmonary edema - 0.06%, PRES - 0.07%, abruptio placenta - 0.14% and maternal death in Group A was 2% and in Group B was 8%. Maternal complications are more in normotensive women (46%) presented with imminent symptoms than in preeclampsia women (26%) with imminent symptoms. Incidence of IUGR in Group A was 46%, whereas in Group B 12%. Incidence of preterm babies in Group A was 18%, whereas in Group B was 42%. Perinatal death incidence was 2.2% in imminent eclampsia. Conclusions: Because known preeclampsia patients were aware of imminent symptoms and presented early to hospital. Early identification and treatment of this dreadful outcome at the imminent state itself can reduce the complications. In current status on preventive aspect of eclampsia, atypical presentation should also be considered for which new screening and diagnostic tools has to be developed.